2021
DOI: 10.3390/jof7030224
|View full text |Cite
|
Sign up to set email alerts
|

Weed-Associated Fungal Endophytes as Biocontrol Agents of Fusarium oxysporum f. sp. cubense TR4 in Cavendish Banana

Abstract: The antagonistic activity of fungal endophytes isolated from weeds growing in Cavendish banana farms was determined against Fusarium oxysporum f. sp. cubense TR4 (Foc TR4) causing Fusarium wilt of Cavendish banana. Forty-nine out of the total 357 fungal endophytes from the roots of weeds exhibited antagonistic activity against Foc TR4. High inhibitory activity at 79.61–99.31% based on dual culture assay was recorded in endophytes Lasiodiplodia theobromae TDC029, Trichoderma asperellum TDC075, Ceratobasidium sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Meanwhile, several fungal endophytes were identified with antagonistic activity against F. oxysporum f. sp. cubense TR4 from isolated weeds growing in Cavendish banana farms [55]. Recent data shows that various new cultivars possess high levels of resistance to Foc TR4 although these studies need replication in different environment and in commercial farms [56].…”
Section: B Fusarium Oxysporum: the Golden Catchmentioning
confidence: 99%
“…Meanwhile, several fungal endophytes were identified with antagonistic activity against F. oxysporum f. sp. cubense TR4 from isolated weeds growing in Cavendish banana farms [55]. Recent data shows that various new cultivars possess high levels of resistance to Foc TR4 although these studies need replication in different environment and in commercial farms [56].…”
Section: B Fusarium Oxysporum: the Golden Catchmentioning
confidence: 99%
“…In the 1990s, TR4 was identified as the causal agent of Fusarium wilt disease infecting Cavendish bananas in Taiwan [2]. The disease caused by TR4 has been reported in 23 countries (predominantly in Southeast Asia, South Asia, Africa, and Latin America) [3]. Moreover, TR4 affected the banana industry and reduced banana yield in the Philippines (FAO 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous study [ 21 , 22 ], instead of conventional fertilizer by alkaline fertilizer could significantly increase soil pH and then reduce the occurrence of banana wilt. Although some studies have also shown that biocontrol has an obvious effect on banana Fusarium wilt [ 10 , 23 , 24 , 25 ], the efficacy will be poor if soil acidity is not improved [ 21 , 22 ]. Biocontrol is one of the hot topics of banana Fusarium wilt control before release of the disease resistant variety.…”
Section: Introductionmentioning
confidence: 99%